Fabrication of electrospun fibers from a waterborne soy‐based polyurethane employing polyethylene oxide as a coformer. Issue 6 (24th August 2020) - Herrán, Rodrigo; Molinari, Fabricio N.; Bilbao, Emanuel; Monsalve, Leandro N.; Amalvy, Javier I.
Abstract: The fabrication of electrospun fibers made from aqueous dispersions of polyurethane obtained from renewable sources is an eco‐friendly method to produce porous membranes for different applications. Polyethylene oxide (PEO) has been already employed in formulations for allowing fiber formation, but its role was not yet completely understood. In this work the fabrication of electrospun fibers made from biobased polyurethane aqueous dispersion with PEO in order to obtain regular fibers is performed. The role of PEO was studied by thermal analysis, infrared and Raman spectroscopy, rheology, and fiber morphology. Polyurethane fibers were obtained only when PEO was added, otherwise the dispersion is electrosprayed and particles are formed. It was observed that PEO modifies the rheology of dispersion and assists coalescence of polyurethane particles. On the other hand, polyurethane fibers conserved their diameter and their homogeneous structure after removal of PEO by immersion in water, which indicates that the distribution of both polymers was even within the fibers. This work provides both an insight on the role of PEO and a route for the fabrication of eco‐friendly biobased polyurethane microfibers from aqueous dispersions. Abstract :